Sound Dramaturgies:: repoliticizing performance - Poulou, Angeliki; Manousakis , Manolis (Revista Brasileira de Estudos da Presença, 2024)
The paper explores the potential of sound to repoliticize theatre and performance. By examining the activity and dramaturgical practices of the multimedia art collective Medea Electronique (Greece), it highlights contradictions of contemporary art, particularly the continuous transition from ‘everything is political’ to ‘no, not everything is political’ and vice versa. From a post-Brechtian perspective, the political function of art lies in preserving the diverse sensibilities at the core of art’s autonomy. This entails avoiding that art be reduced to a post-political gesture or aligning it too closely with everyday aestheticized experiences.